Formulation and Evaluation of Formalin Washer Fluid Preparation from Garlic Peel Waste (Allium sativum L.) - Burhan, Amelia Handayani; Irianto, Iramie Duma Kencana; Azizah, Shyella; Puji, Rian (Journal of Fundamental and Applied Pharmaceutical Science, 2024)
Until 2022, there will still be many salted anchovies that contain formalin. This potential danger can be reduced by reducing the levels of formalin that may be contained in salted anchovies before consumption, one of which is by utilizing the saponin content in garlic peel waste. Garlic peel waste powder is proven to be able to reduce formalin levels in salted anchovies by up to 89.12%. However, the use of powder is less practical, and in a certain period, the powder can rot and emit an unpleasant odor. Therefore, an innovation is needed to transform the powder form into a formalin washer fluid. This study aims to determine the effect of garlic peel extract variation on several parameters evaluating the physical properties of formalin washing liquid. The extraction of garlic peel was done using the maceration method and a 70% ethanol solvent. Washing liquids were prepared using glycerin, PEG400, EDTA, and distilled water with varying extract concentrations. Evaluation of physical properties included organoleptic, pH value, specific gravity, viscosity, clarity, and physical stability of formalin washer fluid. The stability test of the physical properties of the sample liquid was carried out using the cycling test method. The samples were kept in storage conditions with extreme temperatures for 3 cycles. In each cycle, the test preparation was stored for 24 hours at 4±2oC and 24 hours at 40±2oC. The formalin washer fluid produced was in the form of a liquid with a weak to pungent garlic aroma, yellow to dark brown in color, homogeneous, clear, and had a pH value of 4. The more extract is used in the formalin washer fluid, the darker the color and the more pungent the garlic aroma will be. Increasing the concentration of garlic peel extract does not affect the pH and clarity of the preparation. The higher the concentration of extract is, the higher the specific gravity and viscosity will be. The selected formula is the formula with a 1% concentration of garlic peel extract.